Uniform Domains and Uniform Domain Decomposition Property in Real Normed Vector Spaces - Huang, M.; Wang, X. (MATHEMATICA SCANDINAVICA, 2013)
Let E be a real normed vector space with (E)≥ 2, D a proper subdomain of E. In this paper we characterize uniform domains in E in terms of the uniform domain decomposition property. In addition, we discuss the relation between quasiballs and domains with the quasiball decomposition property in R^n.